ChemInform Abstract: Transition‐Metal‐Free Oxidative Aliphatic C—H Azidation. Issue 16 (March 2016) - Zhang, Xiaofei; Yang, Haodong; Tang, Pingping
Abstract: An operationally simple, scalable azidation of aliphatic C—H bonds with methyl 2‐(azidosulfonyl)benzoate is described which tolerates a broad range of functional groups.